Analgesic activity of 4-amino-5-methyl-4H-1,2,4-triazol-3-thiones - Kravchenko, T. V.; Panasenko, O. I.; Knysh, Ye. H.; Кравченко, Тетяна Вікторівна; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Кравченко, Т. В.; Панасенко, А. И.; Кныш, Е. Г. (Запорізький державний медичний університет, 2018)
Nowadays non-steroidal anti-inflammatory drugs have found a wide application in treatment of medical conditions. Despite the clinical effectiveness of non-steroidal anti-inflammatory drugs, their administration is followed by a set of side effects. With aim to reveal the substances with a potency of altering pain threshold in animals, the action of 4-amino-5-methyl-4H-1,2,4-triazol-3-thiones on the nociceptive system in conditions of thermal irritation of rats’ extremities was studied. Aim. Study of the analgesic activity of 4-amino-5-methyl-4H-1,2,4-triazol-3-thiones. Materials and methods. Analgesic activity of the synthesized compounds was evaluated in terms of the set of experiments conducted on white rats of 180–240 g weight. The primary pain threshold after the administration of the substances was assessed using a “hot plate” test, involving a metal plate heated at 55 °C as an irritator. The time of the corresponding response (paw licking, jumping out, squeaking) was measured in seconds. Analgesic activity was assessed by observations of the alterations of pain threshold of the group of studied animals to whom the substances were administrated, comparing results with the control group and expressing them in percent. Results. According to the results, it was concluded that 4-(3,4-dimethoxybenzylideneamino)-5-methyl-4H-1,2,4-triazol-3-thione was the most active compound, which reduced the sensitivity to thermal irritation of extremities in the group of animals by 127.78 %; that said, its activity is higher than reference drug Analgin, which was also evaluated in a “hot plate” test. It was established that substance (IV) was slightly more active than the reference drug Analgin, demonstrating 121.11 % of analgesic activity. Processing of the experimental data revealed some dependencies between the chemical structure and pharmacological activity of the substances of research. Conclusions. The obtained results demonstrate that analgesic activity is existent among the set of 1,2,4-triazole derivatives, which creates preconditions for deeper research of the effectiveness and safety of the most active compounds among the studied ones. Протизапальні засоби широко застосовуються в лікуванні патологічних станів. Попри клінічну ефективність нестероїдних про-тизапальних засобів вони мають побічні ефекти. Тому для виявлення серед синтезованих сполук тих, що здатні змінювати поріг больової чутливості дослідних тварин, вивчили дію 4-аміно-5-метил-4H-1,2,4-тріазол-3-тіонів на центральний компонент ноци-цептивної системи за умов термічного подразнення кінцівок щурів. Мета роботи – вивчення аналгетичної активності 4-аміно-5-метил-4H-1,2,4-тріазол-3-тіонів. Матеріали та методи. Дослідження аналгетичної активності синтезованих сполук здійснили в дослідах на білих щурах масою 180–240 г. Встановлюючи первинний поріг больової чутливості досліджуваних речовин на моделі «гаряча пластина», як подразник використовували закріплену металеву пластину з температурою 55 °С. Обчислювали час відповідної реакції в секундах (облизу¬вання лапок, виплигування, писк). Аналгетичну активність визначали за здатністю речовин змінювати поріг больової чутливості дослідних тварин порівняно з контрольними та виражали у відсотках. Результати. У результаті досліджень встановили, що найактивнішою сполукою виявився 4-(3,4-диметоксибензиліденаміно)-5-ме¬тил-4H-1,2,4-тріазол-3-тіон, який знижував чутливість групи досліджуваних тварин до термічного подразнення кінцівок на 127,78 %, що перевищує препарат порівняння анальгін за дією на моделі «гаряча пластина». Виявили, що ненабагато активнішою, пере¬вершуючи референс-препарат анальгін, є сполука (IV), що мала аналгетичну дію 121,11 %. Проаналізували експериментальні дані та встановили деякі закономірності хімічної будови та фармакологічної дії досліджуваних речовин. Висновки. Дані, що одержали, свідчать про наявність аналгетичної активності в ряду похідних 1,2,4-тріазолу, що створює пере¬думови для поглибленого вивчення ефективності та безпечності найактивніших речовин. Противовоспалительные средства широко применяют в лечении патологических состояний. Несмотря на клиническую эффек-тивность нестероидных противовоспалительных средств, все они имеют побочные эффекты. Поэтому для установления среди синтезированных соединений тех, что способны изменять порог болевой чувствительности экспериментальных животных, изучили действие 4-амино-5-метил-4H-1,2,4-триазол-3-тионов на центральный компонент ноцицептивной системы в условиях термического раздражения конечностей крыс. Цель работы – изучение анальгетической активности 4-амино-5-метил-4H-1,2,4-триазол-3-тиона. Материалы и методы. Исследование анальгетической активности синтезированных соединений осуществлен в опытах на белых крысах массой 180–240 г. При установлении первичного порога болевой чувствительности исследуемых веществ на мо¬дели «горячая пластина» как раздражитель использовали закрепленную металлическую пластину с температурой 55 °С. Время ответной реакции измеряли в секундах (облизывание лапок, выпрыгивание, писк). Анальгетическую активность определяли по способности веществ изменять порог болевой чувствительности опытных животных по сравнению с контрольными и выражали в процентах. Результаты. В результате исследований установлено, что наиболее активным соединением оказался 4-(3,4-диметоксибензили¬денамино)-5-метил-4H-1,2,4-триазол-3-тион, который снижал чувствительность группы исследуемых животных к термическому раздражению конечностей на 127,78 %, превышая препарат сравнения анальгин по действию на модели «горячая пластина». Отмечено, что ненамного активнее, превышая референс-препарат анальгин, соединение (IV), которое проявило анальгетиче¬ский эффект 121,11 %. Проанализированы экспериментальные данные и установлены некоторые закономерности в химическом строении и фармакологическом действии исследуемых веществ. Выводы. Полученные данные свидетельствуют о наличии анальгетической активности в ряду производных 1,2,4-триазола, что создает предпосылки для дальнейшего изучения эффективности и безопасности активных веществ.
Дослідження аналгетичної активності 4-аміно-5-метил-4H-1,2,4-тріазол-3-тіонів
Исследование анальгетической активности 4-амино-5-метил-4H-1,2,4-триазол-3-тионов
Keywords: похідні 1,2,4-тріазолу; нестероїдні протизапальні засоби; 1,2,4-triazole; non-steroidal anti-inflammatory agents; производные 1,2,4-триазола; нестероидные противовоспалительные средства